2019
DOI: 10.1109/jstars.2019.2957919
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of a Troposphere Effect Mitigation Processor for SAR Interferometry

Abstract: Troposphere effect mitigation based on numerical weather prediction (NWP) is an actual research topic in SAR interferometry (InSAR) and especially in persistent scatterer interferometry (PSI). This is the reason, a scientific troposphere effect mitigation processing system has been developed. The objective of this paper is to provide the methodology of four developed algorithms, demonstrate application examples, discuss the methods characteristic and recommend techniques for operational systems. Index Terms-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The atmospheric phase screen (APS) present in interferograms consists of a topography dependent part, and a topography independent part [68]. It has been demonstrated that the topography dependent component of the atmospheric phase screen may be reasonably predicted under certain conditions using only SAR data [69], or using auxiliary numerical weather models [70]. The topography independent part can be further decomposed into a relatively stable part over long spatial scales (> 50 km), and a part due to turbulent mixing with shorter spatial and temporal scales [7].…”
Section: Insar Applications In Norwaymentioning
confidence: 99%
“…The atmospheric phase screen (APS) present in interferograms consists of a topography dependent part, and a topography independent part [68]. It has been demonstrated that the topography dependent component of the atmospheric phase screen may be reasonably predicted under certain conditions using only SAR data [69], or using auxiliary numerical weather models [70]. The topography independent part can be further decomposed into a relatively stable part over long spatial scales (> 50 km), and a part due to turbulent mixing with shorter spatial and temporal scales [7].…”
Section: Insar Applications In Norwaymentioning
confidence: 99%
“…The estimates are relative to a reference point and surface deformations are measured in the satellites line-of-sight (LoS) direction. The wide-area Sentinel-1 PSI processing is performed by a modified version of the PSI GENESIS processor (Adam et al 2013;Goel et al 2016;Adam 2019). The modifications include geodetic corrections, e.g., plate tectonic motion, solid earth tides (Rodriguez Gonzalez et al 2018), and tropospheric phase mitigation by a simulation and subtraction of the tropospheric delay using the ECMWF (European Centre for Medium-Range Weather Forecasts) ERA-5 numerical weather forecast model (Adam 2019).…”
Section: Sentinel-1 Psi Datasetmentioning
confidence: 99%
“…The wide-area Sentinel-1 PSI processing is performed by a modified version of the PSI GENESIS processor (Adam et al 2013;Goel et al 2016;Adam 2019). The modifications include geodetic corrections, e.g., plate tectonic motion, solid earth tides (Rodriguez Gonzalez et al 2018), and tropospheric phase mitigation by a simulation and subtraction of the tropospheric delay using the ECMWF (European Centre for Medium-Range Weather Forecasts) ERA-5 numerical weather forecast model (Adam 2019). The modifications are set-up that it is able to provide a high precision of deformation rate estimates, even over rural areas and large distances, e.g., more than 100 km (Parizzi et al 2021).…”
Section: Sentinel-1 Psi Datasetmentioning
confidence: 99%
“…Sentinel-1 images are processed by means of a wide area PSI approach [27]. Numerical weather forecast data are used to mitigate the troposphere effect in the interferograms and thus, increase the precision of the results [28] A modified version of the 3-arc-second SRTM C-band digital elevation model (DEM) [29] was used to estimate and subtract the topographic phase from the interferograms. Since the BBD is produced from adjacent and overlapping frames, a mosaicking approach is applied to produce a homogeneous national-scale deformation map.…”
Section: Bodenbewegungsdienst Deutschland-germanymentioning
confidence: 99%